1975
DOI: 10.2307/1936162
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Two Populations of Pinus rigida Mill. from the Pine Barrens of New Jersey

Abstract: The Outer Coastal Plain of New Jersey is largely dominated by pitch pine (Pinus rigida) forests. Most of the area supports trees of normal stature (Barrens) but fairly extensive areas of pygmy forest (Plains) also are present. We compared germination and growth characteristics of two populations representing these types. Seeds derived from trees of the contrasting forms were grown under greenhouse—nursery and phytotron conditions for periods up to 5 1/2 yr. Height, growth form, and biomass comparisons were mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…Scrub oak and pitch pine could establish and persist, but would be frequently topkilled. Repeated top-killing fires at 5-20 year intervals select for multi-stemmed, dwarf pitch pines with precocious serotinous cone production (Good and Good, 1975) (Table 2; Fig. 4).…”
Section: Fire Sorting Of Pine Barrens Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scrub oak and pitch pine could establish and persist, but would be frequently topkilled. Repeated top-killing fires at 5-20 year intervals select for multi-stemmed, dwarf pitch pines with precocious serotinous cone production (Good and Good, 1975) (Table 2; Fig. 4).…”
Section: Fire Sorting Of Pine Barrens Speciesmentioning
confidence: 99%
“…Pitch pine seedlings establish readily in pine woodland and forest areas but are slow to appear in clearings in the pine plains, where most cones are serotinous and remain closed without fire. Pines that do establish in clearings in the dwarf pine plains tend to be single-stemmed, taller and straighter than the surrounding dwarf pines, perhaps because they have never been top-killed (Good and Good, 1975). Only 50% of pitch pines on clearings in the dwarf pine plains are serotinous compared with $90% in undisturbed plains (Jordan, unpublished data).…”
Section: Species Responses To Clearingmentioning
confidence: 99%
“…For example, Rogers & Bendich (1987) reported a 12-fold variation within individuals, but almost a 95-fold difference among individuals within a population of Vicia faba. In maize, Buescher et al, (1984), reported a 4.6-fold difference among individuals; while Zhang et al, (1990) found a 6.4-fold difference among individuals The dwarf nature of these populations has been described as an apparent adaptation to higher fire frequencies relative to the other parts of the Pine Barrens, as well as to the distribution range of pitch pine (Ledig & Fryer, 1973;Good & Good, 1975;Givnish, 1981). Thus, while it is reasonable to assume that fire-related stress may have affected both the rDNA copy numbers as well as morphology of individuals of EP and WP populations, AN and WF do not share morphological similarities with the individuals from the Plains' (WP and EP) populations.…”
Section: Resultsmentioning
confidence: 99%
“…Pitch pine shows a large phenotypic amplitude in the Pine Barrens: it grows as a shrub (2-4 m) in the East and West Plains, but attains a height of nearly 30 m in some parts of the ecosystem. The dwarf form in the Pine Plains has been described as an adaptive response to relatively higher fire frequencies (Givnish, 1981 and references therein) In an attempt to study population differentiation between the Plains (dwarf) and the other (tall) populations of the Pine Barrens, Good & Good (1975) conducted a growth study on progeny obtained from the tall and the dwarf forms and found a statistically significant difference in growth rate between the two forms; they therefore suggested that the contrasting growth patterns may be attributable to genetic differences. On the other hand, Guries & Ledig (1978), failed to detect a significant variation in gene frequencies between the tall and the dwarf forms using allozyme markers, which may be explained by high levels of gene flow existing among these populations (Govindaraju,1 989a).…”
Section: Introductionmentioning
confidence: 99%
“…In well QZ-4, the Quercus-Ulmus-Poaceae pollen assemblage is observed in the pollen zone II, and the chernozem soil section is observed in this zone too (Figure 3). Meanwhile, it is known that Pinus prefers cool weather [18]. In the well QZ-4, the Pinus is observed in the both pollen zones.…”
Section: Paleo-temperature Interpretationmentioning
confidence: 99%